2017
DOI: 10.1016/j.clim.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Circulating B cells in type 1 diabetics exhibit fewer maturation-associated phenotypes

Abstract: Although autoantibodies have been used for decades as diagnostic and prognostic markers in type 1 diabetes (T1D), further analysis of developmental abnormalities in B cells could reveal tolerance checkpoint defects that could improve individualized therapy. To evaluate B cell developmental progression in T1D, immunophenotyping was used to classify circulating B cells into transitional, mature naïve, mature activated, and resting memory subsets. Then each subset was analyzed for the expression of additional mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 76 publications
5
26
0
Order By: Relevance
“…It is also notable that we did not detect increased expression levels of CD95 on switched memory B cells, as described previously in individuals with rheumatoid arthritis [26]. Instead, we found that CD95 expression was reduced on switched CD27 + IgD − memory B cells in individuals with long-standing diabetes, consistent with the findings of a recent study by Hanley and colleagues, who also reported lower frequencies of CD24 ++ CD38 ++ B cells in people with type 1 diabetes [27]. This latter phenotype is indicative of regulatory B cells [28], but does not match the profiles we identified in areas 2 and 6 of the SPADE tree, where reduced expression of CD24 was apparent in newly diagnosed individuals and those with long-standing diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…It is also notable that we did not detect increased expression levels of CD95 on switched memory B cells, as described previously in individuals with rheumatoid arthritis [26]. Instead, we found that CD95 expression was reduced on switched CD27 + IgD − memory B cells in individuals with long-standing diabetes, consistent with the findings of a recent study by Hanley and colleagues, who also reported lower frequencies of CD24 ++ CD38 ++ B cells in people with type 1 diabetes [27]. This latter phenotype is indicative of regulatory B cells [28], but does not match the profiles we identified in areas 2 and 6 of the SPADE tree, where reduced expression of CD24 was apparent in newly diagnosed individuals and those with long-standing diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to some previous studies [6,29], in our study the B cell compartment in T1D patients did not differ from controls. However, in one study focusing on patients with long-standing T1D, T1D patients did not differ from controls in most B cell subpopulations, but the expression of maturation-associated markers was impaired in T1D patients [30]. This may indicate that the B cell compartment is largely involved in the T1D pathogenesis through functional defects.…”
Section: Discussionmentioning
confidence: 96%
“…B cells also have regulatory and effector functions mediated by cytokines and chemokines [28]. However, in one study focusing on patients with long-standing T1D, T1D patients did not differ from controls in most B cell subpopulations, but the expression of maturation-associated markers was impaired in T1D patients [30]. However, in one study focusing on patients with long-standing T1D, T1D patients did not differ from controls in most B cell subpopulations, but the expression of maturation-associated markers was impaired in T1D patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations within CD19 + B cell subsets were only found in patients with HT despite that autoantibodies are also present in T1D, GD and AD. Previous studies addressing peripheral B cells in T1D and GD have reported that frequencies were similar compared to HC (32)(33)(34) or that functional responses toward autoantigens were changed (35,36).…”
Section: Discussionmentioning
confidence: 96%